Impact of a Virtual Multidisciplinary Sarcoma Case Conference on Treatment Plan and Survival in a Large Integrated Healthcare System. Issue 11 (November 2021) - Pan, Minggui; Yu, Jeanette; Sidhu, Manpreet; Seto, Tiffany; Fang, Andrew
Abstract : PURPOSE: Quantifying the impact of a multidisciplinary cancer case conference on patient outcome and care quality remains challenging. PATIENTS AND METHODS: We prospectively investigated the impact of our virtual multidisciplinary sarcoma case conference (VMSCC) on treatment plan in patients presented to the VMSCC from July to October 2020 (prospective cohort) and retrospectively in patients with metastatic or locally advanced high-grade soft-tissue sarcoma (STS) reviewed in the VMSCC in 2016 and 2017 (high-grade STS cohort). We also investigated the factors related to the nonadherence to the VMSCC-recommended plan in both cohorts. RESULTS: In both cohorts, approximately 28% of the patients were referred to the VMSCC for review without a treatment plan. In significantly more cases, referring physicians outside of the sarcoma group did not have a plan formulated before the VMSCC review compared with the referring physicians within the sarcoma group. In 28.2% (prospective cohort) and 19.5% (high-grade STS cohort) of the patients, VMSCC recommended a different plan. The adherence to the VMSCC-recommended plan was 87.9% and 83.1%, respectively. The causes of the nonadherence were primarily due to disease progression or patient's decision against recommended therapy. The median overall survival for the high-grade STS cohort was 26 months. CONCLUSION: VMSCC affected the treatment plan in approximately 50% of the patients in both cohorts. The median overall survival of the patients with high-grade STS reviewed by the VMSCC in our cohort is comparable with the literature.